Synthesis of nickel-doped BiVO4 materials by hydrothermal method and evaluation of their photocatalytic ability to decompose methylene blue under visible light - Pham, Van Thinh; Dao, Bach Tuyet T.; Tran, Thi Kim Ngan; Tran, Ngoc Quyen; Bach, Long Giang (Vietnam Journal of Science and Technology, 2024)
Ni-doped BiVO4 photocatalysts were successfully synthesized by hydrothermal method. The catalytic samples were characterized by scanning electron microscopy (SEM), UV-vis diffuse reflection spectroscopy (DRS), photoluminescence spectroscopy (PL) and X-ray diffraction (XRD). Based on the results of PL spectrum analysis, the electron-hole recombination phenomenon is limited by the presence of the second metal Ni in the structure at Bi3+ sites. The catalyst materials at the Ni doping ratios all have the monoclinic-scheelite BiVO4 structure as shown by the XRD and Raman methods. The photocatalytic ability of methyl blue (MB) on the Ni/BiVO4 catalyst was studied under visible light irradiation in order to contribute to reducing the current environmental pollution problem. The removal efficiency of MB varies with the doping ratio of Ni/BiVO4, reaching the highest decomposition efficiency of 84.77 % in the 5 % mol Ni sample, which is 30 % higher than that of the BiVO4 sample. The BiVO4 material modified with Ni giving a high photocatalytic efficiency of organic pigment decomposition under visible light indicates the potential improvement inthe efficiency of a material for existing applications and exploit many new applications in the future.